Crystal Structure of ReCl2(acac)2, ReCl2(acac) [P(C6H5)3]2 and ReOCl2(acac)P(C6H5)3 - Wan, Cheng (My University, 1969)
The crystal structure of ReCl2(acac)2, ReCl2(acac) [P(C6H5)3]2 and ReOCl2(acac)P(C6H5)3 have been determined by single crystal x-ray diffraction methods. The structure of ReCl2(acac)2 has been found to belong to the trans-dichloro-group of the M(acac)2L2 type compounds. In ReCl2(acac)[P(C6H5)3]2, the two phosphorus atoms are trans, and the two chlorine atoms are cis to each other. In RCl2(acac)P(C6H5)3, it has been found that two chlorines are at trans positions and the oxo group and the triphenylphosphine group are cis to each one of the carbonyl oxygen atoms of the acetylacetone group. The bonding of Re-Cl, Re-P, and Re_O are individually discussed and compared. The nature of bonding in the acetylacetone group is also discussed. The intramolecular non-bonded distances between ligand atoms bonded directly to rhenium are compared with other relaxed compounds. The reaction mechanisms for the formation of these three rhenium acetylacetones have been proposed.
Title: Crystal Structure of ReCl2(acac)2, ReCl2(acac) [P(C6H5)3]2 and ReOCl2(acac)P(C6H5)3, Author: Cheng Wan, Location: Thode